Among Digitized Manuscripts. Philology, Codicology, Paleography in a Digital World - van Lit, L.W.C (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2019)
If you work with digital photos of manuscripts or archival materials, Among Digitized Manuscripts provides the conceptual and practical toolbox for you to create a state-of-the-art methodology and workflow. No previous computer knowledge is required. Readership: People working with digital photos of texts, especially handwritten documents such as manuscripts and archive materials.